Designed Synthesis of Nanostructured Materials as the Heterogeneous Catalysts - Kyungsu Na (Nanomaterials, 2022)
The development of nanoscale syntheses and innovative characterization tools resulted in the tailored design of nanostructured materials with versatile abilities in many applications [...]